Effectiveness of Implementation of Hospital Management Information System (Sim-Rs) and Commitment to the Quality of Health Services Towards the Efficiency of Health Services and Its Implications on Patient Satisfaction - Khalda Fakhirah Syahbana; Sri Rochani Mulyani; Abd Halim (PSPP JOURNALS, 2026)
Digital transformation in healthcare requires hospitals to provide effective, efficient, and patient-satisfaction-oriented services. One strategic effort is the implementation of a Hospital Management Information System (SIM-RS), supported by a commitment to quality healthcare services. Analyze the influence of the effectiveness of the implementation of SIM-RS and the commitment to the quality of health services on the efficiency of health services and their implications for patient satisfaction at Ibnu Sina Hospital Makassar. This study uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to respondents and analyzed using path analysis to test the direct and indirect influences between research variables. Shows that the effectiveness of SIM-RS implementation and commitment to quality healthcare services have a positive effect on healthcare service efficiency. Healthcare service efficiency also has a positive effect on patient satisfaction. Furthermore, healthcare service efficiency has been shown to act as a mediating variable in the relationship between SIM-RS implementation effectiveness and commitment to quality healthcare services on patient satisfaction. These findings emphasize that the success of hospital digitalization needs to be balanced with a strengthened commitment to quality to achieve efficient services and optimal patient satisfaction.